2021
DOI: 10.1093/ehjopen/oeab008
|View full text |Cite
|
Sign up to set email alerts
|

Women leaders in Cardiology. Contemporary profile of the WHO European region

Abstract: Aims Women’s participation is steadily growing in medical schools, but they are still not sufficiently represented in cardiology, particularly in cardiology leadership positions. We present the contemporary distribution of women leaders in cardiology departments in the World Health Organization European region. Methods and results Between August and December 2020 we applied purposive sampling to collect data and analyse gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…While the magnitude of the gap may vary between the countries and continents, disparities based on gender and vertical segregation of women in cardiology and CT surgery are pervasive across the globe. Borelli et al performed a gender-based analysis of the distribution of leadership positions within cardiology departments in a cohort of 23 European countries, finding significant disparities similar to the United States ( 20 ). Although different perspectives and hypotheses are postulated for these inequities, the underlying reasons are complex and multifold and differ a great deal depending on the domain of practice, type of practice and level of career.…”
Section: Discussionmentioning
confidence: 99%
“…While the magnitude of the gap may vary between the countries and continents, disparities based on gender and vertical segregation of women in cardiology and CT surgery are pervasive across the globe. Borelli et al performed a gender-based analysis of the distribution of leadership positions within cardiology departments in a cohort of 23 European countries, finding significant disparities similar to the United States ( 20 ). Although different perspectives and hypotheses are postulated for these inequities, the underlying reasons are complex and multifold and differ a great deal depending on the domain of practice, type of practice and level of career.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work performed by the Pink International Young Academy of Cardiology group demonstrated that in Europe, countries with the most national gender parity had the worst representation of female leaders in cardiology. 5 Conversely, Russia and Morocco who have the most female cardiology leaders, have the worst parity in gender nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study found that women were leaders of 30% (254/849) of cardiology departments in Europe. 7 Women leaders were younger than their men counterparts (mean 52 years vs 58 years, respectively) and had significantly fewer scientific publications than men (median 16 publications vs 44 publications, respectively). Considering this evidence, the overall of 37% women as faculty and abstract presenters at the 2021 congress broadly reflects women's general representation within the ESC and in cardiology departments in Europe.…”
Section: The Context Of Women's Representation In Cardiovascular Medi...mentioning
confidence: 97%
“…As of 2021, there are approximately 105 000 members of the ESC (including all association free and paying members, fellows, ESC professional members, national cardiac society members, councils, working group members), of whom 35.7% are women, 60.1% are men and 4.2% are of unknown gender. Furthermore, a recent study found that women were leaders of 30% (254/849) of cardiology departments in Europe 7. Women leaders were younger than their men counterparts (mean 52 years vs 58 years, respectively) and had significantly fewer scientific publications than men (median 16 publications vs 44 publications, respectively).…”
Section: Introductionmentioning
confidence: 99%